A aprendizagem da química e o construtivismo no ensino médio: estudo exploratório em uma escola estadual no município de São Paulo - Lopes, Cleci Geraldo (2006)
The introduction of non-traditional practices to the teaching of chemistry based on construtivism, that privileges an intense participation and an interactiving among students and the teaching staff, has been facilitate the teaching-learning process and has been contributing to acquiring some knowledge related to the chemical phenomenon which take place in nature and in every day activities. This, study aimes to evaluate a non-conventional teaching practice applied to a state high-school level. Therefore, some cinematographical resources and some lab practices has been used in order to arouse students interest in the study of chemistry and physics. Some theoretical reflections about the main foundations of the constructivist proposal related to the teaching of chemistry in the high school networks, based on the studies of Brazilian educators have been developed. The qualitative methodology that has been used is based on a case-study of the exploratory type which has counted on the participation of students belonging to a state school in São Paulo, municipal area. According to the results that have been obtained and the participating students testimony it could be considered that the use of films associated to lab practices has proved to be a motivating resource and, it could be taken as a significative subsidiary mean in the chemical-physical teaching learning process in high school bases in the perspective of the education is interested in the citizenship as it has been recommended by Lei de Diretrizes e Bases da Educação Nacional (Act nº 9.394/96).